Relationship between Chronic Energy Deficiency and Compliance with Taking Fe Tablets with the Incidence of Anemia in Pregnant Women at Kuala Simpang City Health Center Aceh Tamiang - Lina; Arbaiyah; Meliani Sukmadewi Harahap (Science Midwifery, 2022)
Anemia is the biggest public health problem in the world, especially for the reproductive age group. The World Health Organization (WHO), which estimates that 40% of the causes of maternal death in developing countries are related to anemia due to iron deficiency infection. Based on the results of the Basic Health Research (Riskesdas) in 2018, the prevalence of anemia in pregnant women in Indonesia in 2018 was 37.1%, at the Kuala Simpang City Health Center, namely pregnant women in 2018 as many as 338 people. This study aims to determine the relationship between chronic energy deficiency and adherence to consuming Fe tablets with the incidence of anemia in pregnant women. The design of this study used an analytic type with a cross sectional design. This study uses primary data that is processed univariately. The data are presented in the form of frequency distribution tables, cross tables and narratives. The instrument used in this research is a questionnaire which was developed based on the research variables. The number of samples in this study were 56 respondents using the Proportional Stratified Random Sampling technique. The results of this study showed that the majority did not experience anemia as many as 31 (55.4%) respondents. This study concludes that there is a relationship between chronic energy deficiency p-value 0.000 (p<0.05) and adherence to taking tablets with a p-value of 0.000 (p<0.05) with the incidence of anemia in pregnant women. Pregnant women must apply a good diet during pregnancy so that nutrients and nutritional needs during pregnancy can be met and regularly consume Fe tablets.